Controlled acid catalyzed sol gel for the synthesis of highly active TiO2-chitosan nanocomposite and its corresponding photocatalytic activity - Afzal, S.; Samsudin, E.M.; Julkapli, N.M.; Hamid, Sharifah Bee Abd (Springer Verlag (Germany), 2016)
For the synthesis of a highly active TiO2-chitosan nanocomposite, pH plays a crucial role towards controlling its morphology, size, crystallinity, thermal stability, and surface adsorption properties. The presence of chitosan (CS) biopolymer facilitates greater sustainability to the photoexcited electrons and holes on the catalysts’ surface. The variation of synthesis pH from 2 to 5 resulted in different physico-chemical and photocatalytic properties, whereby a pH of 3 resulted in TiO2-chitosan nanocomposite with the highest photocatalytic degradation (above 99 %) of methylene orange (MO) dye. This was attributed to the efficient surface absorption properties, high crystallinity, and the presence of reactive surfaces of –NH2 and –OH groups, which enhances the adsorption-photodegradation effect. The larger surface oxygen vacancies coupled with reduced electron-hole recombination further enhanced the photocatalytic activity. It is undeniable that the pH during synthesis is critical towards the development of the properties of the TiO2-chitosan nanocomposite for the enhancement of photocatalytic activity.